Competitive intelligence collection and use by sales and service representatives: how managers’ recognition and autonomy moderate individual performance - Rapp, Adam; Agnihotri, Raj; Baker, Thomas L.; Andzulis, James ‘Mick’ (Journal of the Academy of Marketing Science, 2015)
The importance of knowledge to the organization cannot be denied. However, to date little research has investigated the critical role individuals in sales and service representative positions play in the gathering and use of information in the organization and how this information can help them enhance their performance. Using social identity theory as a conceptual background, this paper reports two studies which investigate how organizational identification and role conflict impact the collection and use of individual competitive intelligence (ICI) and how this impacts individual performance. In addition, we look at the impact of managerial recognition and autonomy on these relationships. Tests across two firms using hierarchical linear modeling provide support for the hypothesized relationships. We conclude that firms can create an environment which facilitates the collection and use of ICI and that this, in turn, positively impacts individual performance.